Die aanpassing en uitbreiding van die verteenwoordigingsreg ten einde die maatskappy as afsonderlike regspersoon te pas - Retief, Gerhard Johann (Department of Commercial Law, 2021)
The General Laws of Agency do not supply a full answer in circumstances where the principal is a company. These laws have undergone certain changes and extentions to suit the company which, as principal, cannot perform any act, by reason of the fact that it is a fictious entity. These changes were brought about by the English Doctrine of Constructive Notice and the Turquand Rule, as well as Section 36 of the Companies Act (Changes); and the Doctrine of Estoppel (Extention). Abolition of the Doctrine of Constructive Notice and the Ultra Vires Doctrine is pleaded on the one hand and the retention of the Turquand Rule, which must be kept distinct from Estoppel, on the other. Contracting with companies will hereby be simplified and become more practical. This will bring our company law on par with modern company law developments, especially those of England.